2022
DOI: 10.32604/jrm.2022.021694
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Waterproofness of Concrete and Alkali-Aggregate Using Hydrophobic Impregnation and Coating

Abstract: Part of the tunnel spoil can not be used for concrete due to alkali-aggregate reaction (AAR). Water is an indispensable condition for AAR, so separating the alkali-aggregate from water is of great benefit to controlling the AAR. This paper investigates the modification of concrete and aggregate by hydrophobic impregnation and organic coating and then evaluates their waterproof and mechanical properties by dynamic contact angle (DCA), ultrasonic wave velocity, scanning electron microscope (SEM), nuclear magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…It was reported that pores with the size larger than 200 nm were defined as harmful pores [33,34]. The proportion of harmful pores in concrete with 0.5%, 0.75%, and 1.25% superplasticizer content reach 48.11%, 50.64%, and 61.46%, respectively, because the high dosage of superplasticizer would bring more air bubbles into the concrete.…”
Section: Pore Characteristicsmentioning
confidence: 99%
“…It was reported that pores with the size larger than 200 nm were defined as harmful pores [33,34]. The proportion of harmful pores in concrete with 0.5%, 0.75%, and 1.25% superplasticizer content reach 48.11%, 50.64%, and 61.46%, respectively, because the high dosage of superplasticizer would bring more air bubbles into the concrete.…”
Section: Pore Characteristicsmentioning
confidence: 99%